-2-8=-7+x

Simple and best practice solution for -2-8=-7+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2-8=-7+x equation:


Simplifying
-2 + -8 = -7 + x

Combine like terms: -2 + -8 = -10
-10 = -7 + x

Solving
-10 = -7 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-10 + -1x = -7 + x + -1x

Combine like terms: x + -1x = 0
-10 + -1x = -7 + 0
-10 + -1x = -7

Add '10' to each side of the equation.
-10 + 10 + -1x = -7 + 10

Combine like terms: -10 + 10 = 0
0 + -1x = -7 + 10
-1x = -7 + 10

Combine like terms: -7 + 10 = 3
-1x = 3

Divide each side by '-1'.
x = -3

Simplifying
x = -3

See similar equations:

| 18=not-18 | | 4/7×21/40 | | 8a-(16/12a)=14 | | 2/i= | | d=5(55) | | 2x-3*2= | | 4x-9y-6x+6y= | | 5-2ab-3bc+a*3b-c*b*4= | | 17/3x=1 | | 5x+5+3x+13=90 | | 2.6(m+1.9)=22 | | 5000/x=300 | | -2y=x-3 | | 2727/g=27 | | 6x-1=x+28 | | f(x)=-x^2+10-2 | | ln(2x-4)=ln(x+5) | | 6x-(3x+8)=3x | | -6b+6=-5b | | 8y-2=10y-32 | | -5-4(p+7)=-39-p | | -7s=-8-8s | | 10+6x=20+2(3x-5) | | 1(1-3x)+4(2x-5)=-24 | | 3q+8=5q | | p=12.50+4a | | 7*X= | | 7/3x-1/7=5 | | s-6=p | | 8-6g=-7g | | -2v+-5v=-19 | | 9+Z=41 |

Equations solver categories